Primary extragonadal yolk sac tumor of the orbit: A rare case and review of literature (Indian Journal of Case Reports, 2024)
Germ cell tumors usually arise from primordial cells in gonads, mainly testes, and ovaries. Extragonadal involvement of orbit is very unusual. We report one case of primary yolk sac tumor of orbit in a 3-year-old male child presented as a left lateral orbital mass. Its clinical presentation may mimic many common pediatric orbital tumors causing misdiagnosis which affects ocular morbidity and mortality. Awareness about this rare entity to clinicians is helpful in the early diagnosis and proper management of young kids.